Systematic review on evaluating planning process in agile development methods - Iqbal Ahmed (Universitas Ahmad Dahlan, 2020)
Agile development methods have been catering the need of faster delivery of theever-demanding domain of software engineering. These methods are able to deliver value to users and businesses via fast, reliable, and repeatable process. Planning requirements and processes takes the driving seat in a dynamic environment because the value proposition rapidly changes. This paper exhibits asystematic literature review of planning processes implementedby various agile methods in order to find the best suited agile method in terms of robust planning. Keywords: It was found that Scrum is the best suited agile method for planning processes.